Membangun Kualitas Hubungan Untuk Meningkatkan Kinerja Tenaga Penjual Di AHASS Honda Yogyakarta - Ida Bagus Nyoman Udayana; Ardi Gusmawan (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
This study aims to examine the effect of Adaptive Selling Behavior and Customer Orientation against Salesperson Performance through Relationship Quality. This research was conducted in 145 respondents sales in AHASS Yogyakarta. The results of this study show: 1) Adaptive selling behavior significant positive effect on Relationship Quality, 2) Customer Orientation Significant positive effect on Relationship behavior, 3) Relationship quality significant positive effect on Salesperson Performance, 4) Adaptive Selling Behavior significant positive effect on Salesperson Performance, 5) Customer Orientation significant positive effect on Salesperson Performance,.